PP1γ2 and PPP1R11 Are Parts of a Multimeric Complex in Developing Testicular Germ Cells in which their Steady State Levels Are Reciprocally Related - Cheng, Lina (Public Library of Science, 2009)
Mice lacking the protein phosphatase 1 gamma isoforms, PP1γ1 and PP1γ2, are male-sterile due to defective germ cell morphogenesis and apoptosis. However, this deficiency causes no obvious abnormality in other tissues. A biochemical approach was employed to learn how expression versus deficiency of PP1γ2, the predominant PP1 isoform in male germ cells, affects spermatogenesis. Methods used in this study include column chromatography, western blot and northern blot analyses, GST pull-down assays, immunoprecipitation, non-denaturing gel electrophoresis, phosphatase enzyme assays, protein sequencing, and immunohistochemistry. We report for the first time that in wild-type testis, PP1γ2 forms an inactive complex with actin, protein phosphatase 1 regulatory subunit 7 (PPP1R7), and protein phosphatase 1 regulatory subunit 11 (PPP1R11), the latter, a potent PP1 inhibitor. Interestingly, PPP1R11 protein, but not its mRNA level, falls significantly in PP1γ-null testis where mature sperm are virtually absent. Conversely, both mature sperm numbers and the PPP1R11 level increase substantially in PP1γ-null testis expressing transgenic PP1γ2. PPP1R11 also appears to be ubiquitinated in PP1γ-null testis. The levels of PP1γ2 and PPP1R11 were increased in phenotypically normal PP1α-null testis. However, in PP1α-null spleen, where PP1γ2 normally is not expressed, PPP1R11 levels remained unchanged. Our data clearly show a direct reciprocal relationship between the levels of the protein phosphatase isoform PP1γ2 and its regulator PPP1R11, and suggest that complex formation between these polypeptides in testis may prevent proteolysis of PPP1R11 and thus, germ cell apoptosis.